2022
DOI: 10.1002/adpr.202200195
|View full text |Cite
|
Sign up to set email alerts
|

Dual Hybridized Local and Charge Transfer Characteristic Fluorophore as an Efficient Nondoped Emitter for Electroluminescent Device

Abstract: Hybridized local and charge transfer (HLCT) is an attractive strategy for achieving efficient electroluminescence (EL) in electrofluorescent devices by the conversion of triplet‐state (T) to singlet‐state (S) excitons via a reverse intersystem crossing, giving rise to a high exciton utilization efficiency exceeding the spin statistical limit. Excellent device performance is reached using thermally evaporated emissive layers. However, for potential large‐scale commercialization, it is crucial to attain comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…As can be seen, 2MIQ-NPA shows a single linear relationship over the entire solvent polarity, defining that the excited state dipole ( μ e ) calculated by the Lippert–Mataga equation is only 2.27 D. Previous studies have suggested that when the excited state dipole is greater than 10 D, it can be assigned as CT characteristics. 17,37 However, our NTO and experimental results indicate that the LE characteristic is dominant in the singlet excited state of 2MIQ-NPA .…”
Section: Resultsmentioning
confidence: 69%
“…As can be seen, 2MIQ-NPA shows a single linear relationship over the entire solvent polarity, defining that the excited state dipole ( μ e ) calculated by the Lippert–Mataga equation is only 2.27 D. Previous studies have suggested that when the excited state dipole is greater than 10 D, it can be assigned as CT characteristics. 17,37 However, our NTO and experimental results indicate that the LE characteristic is dominant in the singlet excited state of 2MIQ-NPA .…”
Section: Resultsmentioning
confidence: 69%
“…Accordingly, HLCT-based OLEDs can achieve efficiencies above the spin statistical limit or an external quantum efficiency (EQE) of >5%, whereas the inherent short exciton lifetime of HLCT emitters owing to the faster rate of RISC brings about a small efficiency roll-off in the devices. 10 To date, many HLCT-based blue OLEDs with high EQEs with Commission Internationale de l’Eclairage (CIE y ) of (0.06–0.30) have been reported; 10 b ,11 however, deep blue HLCT materials that simultaneously bring about high EQE, good color purity and low-efficiency roll-off, particularly at high luminance are still rare. 10 c ,12…”
Section: Introductionmentioning
confidence: 99%
“…Phenanthroimidazole (PI) is a common building block for blue-emissive fluorescent materials, especially HLCT blue-emissive materials, due to its bipolar nature and appropriate energy level. 10 a ,13 In most PI-based HLCT materials, PI is employed as an electron acceptor and integrated with triarylamine-based donors (triphenylamine and carbazole). 10 a ,13 a Some of them produced high-performance non-doped deep blue OLEDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, based on this concept, several D-A-type fluorophores have been designed and investigated including some DR/NIR materials [37][38][39][40][41]. Inevitably, these materials displayed high PLQY and exceptional OLED device performance [42][43][44][45]. Even though the radiative transition rate is improved for the HLCT fluorophores, the non-radiative transition process is still an obstacle to lowering the PLQY, particularly for the DR/NIR emitters [20,46].…”
Section: Introductionmentioning
confidence: 99%